2022
DOI: 10.3389/fendo.2022.961717
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations between thyroid dysfunction and COVID-19 susceptibility and severity: A bidirectional Mendelian randomization study

Abstract: BackgroundObservational studies have reported an association between coronavirus disease 2019 (COVID-19) risk and thyroid dysfunction, but without a clear causal relationship. We attempted to evaluate the association between thyroid function and COVID-19 risk using a bidirectional two-sample Mendelian randomization (MR) analysis.MethodsSummary statistics on the characteristics of thyroid dysfunction (hypothyroidism and hyperthyroidism) were obtained from the ThyroidOmics Consortium. Genome-wide association stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“… 8 A recent study concluded that COVID-19 susceptibility and its severity might increase the risk of hypothyroidism including subclinical hypothyroidism. 9 , 10 This is similar to another study conducted in Bosnia, where they found a significant difference in the number of patients with hypothyroidism and subclinical hypothyroidism in 2020 and 2021 in comparison to 2019. 11 About 78.3% of patients had subclinical hypothyroidism 2 months post-COVID-19 infection in those with thyroid dysfunction which the persisted in 33.6% of the subjects of the patients after one month of follow up which was higher compared to our study.…”
Section: Discussionsupporting
confidence: 88%
“… 8 A recent study concluded that COVID-19 susceptibility and its severity might increase the risk of hypothyroidism including subclinical hypothyroidism. 9 , 10 This is similar to another study conducted in Bosnia, where they found a significant difference in the number of patients with hypothyroidism and subclinical hypothyroidism in 2020 and 2021 in comparison to 2019. 11 About 78.3% of patients had subclinical hypothyroidism 2 months post-COVID-19 infection in those with thyroid dysfunction which the persisted in 33.6% of the subjects of the patients after one month of follow up which was higher compared to our study.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in alignment with previous cross-sectional studies [ 12 , 62 , 63 , 64 ], indicating that alterations in isolated thyroid function indicators alone may not be sufficient to reliably predict the development of viral pneumonia or COVID-19. Prior to this study, four MR investigations examined the relationship between thyroid hormones and COVID-19, utilizing data from the fifth round of the Human Genetics of Infectious Diseases (HGI) releases [ 31 , 65 , 66 , 67 ]. In 2023, Sun et al employed an MR model to assess the causal link between TSH levels and three COVID-19 phenotypes and concluded that there was no association between TSH and COVID-19 [ 65 ], a conclusion consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…To test for horizontal pleiotropy, we used MR-Egger intercept and MR-pleiotropy residual sum and outlier (MR-PRESSO) global test methods [24]. If the P value is > 0.05 and the MR Egger intercept term tends to zero as the sample size increases, this indicates the absence of horizontal pleiotropy [25]. Besides, we used MR-Egger and inverse variance weighted (IVW) in Cochran's Q statistic to test the heterogeneity of genetic IVs and provide evidence of heterogeneity due to pleiotropy or other causes [26].…”
Section: Sensitivity Analysismentioning
confidence: 99%